Early outcomes comparing induction with antithymocyte globulin vs alemtuzumab in two steroid‐avoidance protocols in pediatric renal transplantation. (29th February 2020) - Puliyanda, Dechu P.; Pizzo, Helen; Rodig, Nancy; Somers, Michael J. G.
Abstract: Steroid avoidance in pediatric kidney transplants was found effective with extended daclizumab induction. Upon discontinuation of daclizumab, lymphocyte‐depleting agents became used, with little comparative data. We assessed outcomes in children undergoing low immunologic‐risk deceased donor (DD) kidney transplants using induction with antithymocyte globulin (ATG) compared to alemtuzumab. We reviewed consecutive DD kidney transplants from January 2015 to September 2017 at two pediatric centers that used different lymphocyte‐depleting agents in steroid‐avoidance protocols: ATG (Center A) and alemtuzumab (Center B), with tacrolimus and MMF as maintenance immunosuppression. Anti‐infective prophylaxis was based on center protocol. Over the first year post‐tx, there were similar rates of infections. EBV and BK viremia were comparable though Center A manifested more low‐grade CMV viremia (A 46% vs B 0%; P  = .0009) at median onset 1.8 months, followed by early seroconversion. Reduction of immunosuppression did not differ between groups. DSA at 1 year was similar (A 8% vs 13%) with low rates of BPAR. Need for steroid‐based conversion was low. There were no graft losses and no differences in median eGFR at 30, 90, 180, and 365 days. (a) 1‐year graft outcomes are excellent in steroid‐avoidance regimens using ATG or alemtuzumab induction; (b) conversion to steroid‐based therapy is low; (c) alemtuzumab/high‐dose MMF is associated with lower WBC and more GCSF use; (d) alemtuzumab/higher dose MMF results in more diarrhea and azathioprine conversion than ATG/lower dose MMF; (e) CMV viremia is seen more often with ATG use with infection prophylaxis reduction; however, seroconversion occurs promptly.